2013
DOI: 10.1080/13647830.2013.781224
|View full text |Cite
|
Sign up to set email alerts
|

Buoyancy induced limits for nanoparticle synthesis experiments in horizontal premixed low-pressure flat-flame reactors

Abstract: Premixed low-pressure flat-flame reactors can be used to investigate the synthesis of nanoparticles. The present work examines the flow field inside such a reactor during the formation of carbon (soot) and iron oxide (from Fe(CO) 5 ) nanoparticles, and how it affects the measurements of nanoparticle size distribution. The symmetry of the flow and the impact of buoyancy were analysed by three-dimensional simulations and the nanoparticle size distribution was obtained by particle mass spectrometry (PMS) via mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…A few years later, Hecht et al 12 used Fe-LIF measurements to quantify the iron atom concentration downstream the burner head. In contrast to the previous investigations with a horizontal flow direction leading to unwanted convection, the orientation of the Duisburg reactor is now bottom-up following the recommendations of Weise et al 13 to avoid buoyancy effects. The main reactor chamber has a diameter of 100 mm with four windows enabling optical access.…”
Section: Methodsmentioning
confidence: 99%
“…A few years later, Hecht et al 12 used Fe-LIF measurements to quantify the iron atom concentration downstream the burner head. In contrast to the previous investigations with a horizontal flow direction leading to unwanted convection, the orientation of the Duisburg reactor is now bottom-up following the recommendations of Weise et al 13 to avoid buoyancy effects. The main reactor chamber has a diameter of 100 mm with four windows enabling optical access.…”
Section: Methodsmentioning
confidence: 99%
“…Given the constraints imposed by the existing iPEPICO spectrometer, the burner chamber had to be aligned horizontally, even though non-negligible buoyancy effects have been shown to affect measurements at large distances (>100 mm) between burner and sampling probe in a similar setup used for nanoparticle synthesis. 14 The effect of buoyancy on measurements close to the burner is small and does not typically change flame chemistry conclusions.…”
Section: A Low-pressure Flame and Molecular-beam Samplingmentioning
confidence: 99%
“…Because the zone of particle formation is usually located further downstream, this additional information is indispensable, as shown in Figure 13. 26 Shortly thereafter, Weise et al 11 demonstrated the impact of buoyancy for different reactor/burner orientations with respect to gravity. Using detailed CFD simulations and the previously postulated model, 26 they were able to attribute discontinuities in the Fe 2 O 3 particle growth measurements exclusively to the flow field distorted by buoyancy (see Figure 14).…”
Section: Modeling Of Iron Oxide Formationmentioning
confidence: 99%